MANAJEMEN PENGEMBANGAN KEWIRAUSAHAAN DI PONDOK PESANTREN (Studi Kasus Di Pondok Pesantren Bahrul Maghfiroh Malang) - Wildtan Habibi; Rahmatullah Rahmatullah (STAI Ma'had Aly Al-Hikam Malang, 2019)
Â Entrepreneurship development management in boarding schools is a form of economic independence boarding schools. Islamic Boarding School is an educational institution that has the function of printing human resources as a whole, has expertise in religious knowledge, general science, and entrepreneurship as an effort to equip students with the skills to face the challenges of the times. The development of entrepreneurship at the Bahrul Maghfiroh Islamic boarding school is an actualization of the role of the Islamic boarding school as an independent institution and a printer of superior human resources. The issue that will be examined is how the management of entrepreneurship development in the Bahrul Maghfiroh Islamic boarding school in Malang, as well as several supporting and inhibiting factors in entrepreneurship development in the Bahrul Maghfiroh Islamic boarding school.This research is a case study with qualitative descriptive research. Data obtained from research subjects such as caregivers, business unit heads, board administrators and students managing business units Bahrul Maghfiroh Islamic Boarding School. Data analysis techniques used in this study are data condensation, data presentation and then drawing conclusions by paying attention to findings in the field with theory.Based on the research that has been done, the results show that, first, entrepreneurial development management in Bahrul Maghfiroh Islamic boarding school through four management functions (1) Development planning, (2) Organizing, (3) Implementation, and (4) Supervision. Second, supporting factors for entrepreneurship development at Bahrul Maghfiroh Islamic boarding school are (1) caregiver support, (2) entrepreneurship curriculum, (3) assistance from academics, and (5) adequate infrastructure. The inhibiting factors are (1) there is no structure of the business unit, (2) funding constraints, and (3) the relatively short time allocation of entrepreneurship development